Threats to safe transitions from hospital to home: a consensus study in North West London primary care - Markiewicz,O; Lavelle,M; Lorencatto,F; Judah,G; Ashrafian,H; Darzi,A (British Journal of General Practice, 2020)
Background Transitions between healthcare settings are vulnerable points for patients.Aim To identify key threats to safe patient transitions from hospital to primary care settings.Design and setting Three-round web-based Delphi consensus process among clinical and non-clinical staff from 39 primary care practices in North West London, England.Method Round 1 was a free-text idea-generating round. Rounds 2 and 3 were consensus-obtaining rating rounds. Practices were encouraged to complete the questionnaires at team meetings. Aggregate ratings of perceived level of importance for each threat were calculated (1–3: ‘not important’, 4–6: ‘somewhat important’, 7–9: ‘very important’). Percentage of votes cast for each patient or medication group were recorded; consensus was defined as ≥75%.Results A total of 39 practices completed round 1, 36/39 (92%) completed round 2, and 30/36 (83%) completed round 3. Round 1 identified nine threats encompassing problems involving communication, service organisation, medication provision, and patients who were most at risk. ‘Poor quality of handover instructions from secondary to primary care teams’ achieved the highest rating (mean rating at round 3 = 8.43) and a 100% consensus that it was a ‘very important’ threat. Older individuals (97%) and patients with complex medical problems taking >5 medications (80%) were voted the most vulnerable. Anticoagulants (77%) were considered to pose the greatest risk to patients.Conclusion This study identified specific threats to safe patient transitions from hospital to primary care, providing policymakers and healthcare providers with targets for quality improvement strategies. Further work would need to identify factors underpinning these threats so that interventions can be tailored to the relevant behavioural and environmental contexts in which these threats arise.